Toward a Doctrine of Socially Responsible Marketing (SRM): A Macro and Normative-Ethical Perspective - Laczniak, Gene; Shultz, Clifford (Journal of macromarketing, 2021)
In this conceptual article, the authors use a macro-level analysis and normative ethical theory to delineate and to explicate a doctrine of socially responsible marketing (SRM). Applying a theory-in-formation approach, we postulate a literature-informed definition of SRM. We discuss why a macro and normative-ethical rather than a micro and positive-descriptive perspective is essential to justifying the elements of SRM. We explore and explain why the roots of an authentic doctrine of SRM can be discerned from the literatures of marketing history, corporate social responsibility, institutional economics and moral philosophy. In so doing, the mandate to engage in socially responsible marketing is shown to be anchored in a social contract. This conception offers three essential elements of SRM—corporate citizenship, stakeholder orientation and social/ecological sustainability—each of which augers a pro-social rather than instrumental-financial approach to marketing practice. We recommend a specific normative-ethical standard, embodied in distributive justice, to best evaluate SRM. We counsel adopting a macromarketing perspective of constructive engagement for those seeking responsible marketing for a better society and world. Finally, we offer a short research agenda for advancing Marketing’s embrace of SRM.